1998
DOI: 10.1063/1.120866
|View full text |Cite
|
Sign up to set email alerts
|

Local environment of erbium atoms in amorphous hydrogenated silicon

Abstract: The Er169(169Tm)emission Mössbauer spectroscopy has evidenced that photoluminescence centers in Er-doped amorphous hydrogenated silicon are [Er–O] clusters. The local environment of the Er3+ ions in the clusters is similar to the Er3+ environment in Er2O3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…Masterov et al found the local chemical environment of the optically activated Er-O cluster similar to that of Er 2 O 3 by 169 Er͑ 169 Tm) Mössbauer emission from Er-doped amorphous hydrogenated Si. 41 Hafidi et al found that the Er 4d core level peak in x-ray photoelectron spectroscopy was accompanied by a similar chemical shift for thermally annealed film of a mixing of Si, Er, and O and Er 2 O 3 , indicating the formation of the sixfold coordination of O in both samples. 42 For more quantitative discussion of this structure, the k 3 weighted-EXAFS spectrum, k 3 , of optically activated Si:Er thin film is calculated as shown in the inset in Fig.…”
Section: Experiments and Local Structure Analysismentioning
confidence: 93%
“…Masterov et al found the local chemical environment of the optically activated Er-O cluster similar to that of Er 2 O 3 by 169 Er͑ 169 Tm) Mössbauer emission from Er-doped amorphous hydrogenated Si. 41 Hafidi et al found that the Er 4d core level peak in x-ray photoelectron spectroscopy was accompanied by a similar chemical shift for thermally annealed film of a mixing of Si, Er, and O and Er 2 O 3 , indicating the formation of the sixfold coordination of O in both samples. 42 For more quantitative discussion of this structure, the k 3 weighted-EXAFS spectrum, k 3 , of optically activated Si:Er thin film is calculated as shown in the inset in Fig.…”
Section: Experiments and Local Structure Analysismentioning
confidence: 93%
“…However, most of the studies on the erbium-doped a-SiO x :H to date are mainly focused on the Er 3ϩ emitting centers, i.e., on the chemical environment of Er 3ϩ ions. 5,6 Few reports on the correlation between Er 3ϩ emission and the microstructure in the erbiumdoped a-SiO x :H film can be found. a-SiO x :H, under proper preparation conditions or annealing conditions, is a mixture of two phases: a-Si clusters and SiO x matrix.…”
Section: Introductionmentioning
confidence: 98%
“…Of particular interest, the 4 I 13/2 → 4 I 15/2 transition from the first-excited to the fundamental state emits photons with a wavelength of 1.54 m, which corresponds to the window of minimum attenuation in the silica-based optical fibers commonly used in the optical communications. Er 3ϩ ions have been inserted into different hosts: Crystalline ͑c-͒ silicon, 1,2 hydrogenated amorphous silicon suboxide (a-SiO x :H), [3][4][5][6] Si nanocrystals ͑nc-Si͒ embedded in SiO 2 matrix ͑NCSO͒, [7][8][9][10][11] GaN, 12 TiO 2 , 13 and ZnO, 14 etc. Among these works, the NCSO is one of the most attractive hosts because the Er 3ϩ emission intensity from it is two orders of magnitude stronger than that from the erbium-doped SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a dramatic reduction of the fraction of Er atoms in Si tetrahedral cages in Cz silicon has been associated with the reaction of Er with O during annealing and formation of Er-O complexes [12]. In Er doped a-Si:H, the only study of the local Er environment has been by emission Mössbauer spectroscopy [13]. This study concluded that the Er 31 environment in a-Si:H is similar to that in Er 2 O 3 .…”
mentioning
confidence: 99%